Pulsed dielectric spectroscopy of supercooled liquids - Böhmer, Roland; Schiener, B.; Hemberger, J.; Chamberlin, R. V. (Springer-Verlag, 1995)
Pulsed dielectric spectroscopy is introduced as a technique for selectively emphasizing specific components of the non-exponential dielectric response of matter. Samples studied include supercooled liquid propanol, propylene carbonate, and poly(lauryl-methacrylate). It is shown that particular sequences of pulses can be used to emphasize the fast response regime, to produce a crossover or memory effect, or to eliminate the response of selected components. Furthermore, for materials characterized by broad distributions of relaxation times, the technique facilitates the investigation of a relatively narrow band from that distribution. It is also shown that the time domain spectroscopy can be combined with conventional frequency domain techniques to provide the characterization of dielectric response over an extraordinarily broad spectral range.
Keywords: 530